Amelioration of glomerulosclerosis with all-trans retinoic acid is linked to decreased plasminogen activator inhibitor-1 and α-smooth muscle actin - Liu Xia; Lü Lei; Tao Bei-bei; Zhou Ai-ling; Zhu Yi-chun (Acta Pharmacologica Sinica, 2016)
Aim: To examine the effects of all-trans retinoic acid (atRA) on renal morphology and function as well as on renal plasminogen activator inhibitor-1 (PAI-1) expression and plasmin activity in rats with 5/6 nephrectomy. Methods: Adult male Sprague Dawley rats were given 5/6 nephrectomy or sham operation. Renal function was measured 2 weeks later. The nephrectomized rats were assigned to groups matched for proteinuria and treated with vehicle or atRA (5 or 10 mg/kg by gastric gavage once daily) for the next 12 weeks. Rats with sham operation were treated with vehicle. At the end of the treatments, kidneys were collected for histological examination, Western blot analysis, and enzymatic activity measurements. Results: The 5/6 nephrectomy promoted hypertension, renal dysfunction, and glomerulosclerosis. These changes were significantly reduced in the atRA-treated group. The expressions of PAI-1 and α-smooth muscle actin (α-SMA) were significantly increased in the vehicle-treated nephrectomized rats. Treatment with atRA significantly reduced the expressions of PAI-1 and α-SMA. However, plasmin activity remained unchanged following atRA treatment. Conclusion: Treatment with atRA ameliorates glomerulosclerosis and improves renal function in rats with 5/6 nephrectomy. This is associated with a decrease in PAI-1 and α-SMA, but not with a change in plasmin activity.